Neighborhood environment and cognitive functioning in middle-aged and older population: A mediating role of physical activity - Dalecká, A; Kšiňan, A; Szabó, D; Čapková, N; Pikhart, H; Bobák, M (International journal of hygiene and environmental health, 2025)
BACKGROUND: Evidence on the impact of complex neighborhood environment, including air pollution, greenness, and neighborhood socioeconomic deprivation (nSED) on cognitive health in older adults remains scarce. Both cognition and neighborhood environment are associated with physical activity, but little is known about the potential mediating role of physical activity in this association. METHODS: Cross-sectional data of the Czech arm of the HAPIEE cohort study examined 4,178 participants (55.6% women) aged 45-69 years. Global cognitive score was constructed from memory, verbal fluency, and concentration domains. The exposures, assigned to participant's addresses, include 4-year (2000-2003) average concentrations of PM2.5, greenness index calculated from tree crown canopy cover estimation (2000), and census-based nSED characteristics. Physical activity and other covariates were assessed by a questionnaire. Structural equation modelling was used to estimate standardized β coefficients for the relationships between neighborhood environment, physical activity and cognitive performance. RESULTS: After controlling for a range of covariates, global cognitive function was inversely associated with PM2.5 (β = -0.087; 95%CI: 0.122 to -0.052) and nSED (β = -0.147; 95%CI: 0.182 to -0.115), and positively associated with greenness (β = 0.036; 95%CI: 0.001 to 0.069). We identified a weak but statistically significant mediating role of physical activity in the associations of PM2.5 exposures and nSED on global cognitive score. Total mediation proportions ranged from 3.9% to 6.5% for nSED and PM2.5, respectively. CONCLUSIONS: The neighborhood environment was associated with cognitive health in older individuals; the associations were partially mediated by physical activity.
Keywords: Neighborhood Characteristics; pevné částice; Socioeconomic deprivation; Female; charakteristiky bydlení; ženské pohlaví; charakteristiky okolí bydliště; průřezové studie; znečištění ovzduší; lidé; Air Pollution; cvičení; Ambient air pollution; Particulate Matter; Physical activity; kognice; Residence Characteristics; Cross-Sectional Studies; Greenness; Male; Air Pollutants; Aged; Czech Republic; Socioeconomic Factors; Cognition; Cognitive function; vystavení vlivu životního prostředí; Česká republika; lidé středního věku; socioekonomické faktory; senioři; mužské pohlaví; látky znečišťující vzduch; Exercise; Environmental Exposure; Middle Aged; Humans